Body and Decoloniality in Scenic Poetic composition - Simão (Universidade Federal da Integração Latino-Americana – Foz do Iguaçu/PR, Brazil), Marina Fazzio; Sampaio (Universidade Federal do Tocantins – UFT, Palmas/TO, Brazil), Juliano Casimiro de Camargo (Revista Brasileira de Estudos da Presença, 2022)
Body and Decoloniality in Scenic Poetic Composition - The text is situated between the arts, anthropology and philosophy and aims to answer the question: can the artistic process be understood as a means of decoloniality of ordinary body? Methodologically literature review was carried out an artistic process was analyzed that the authors participated in. It emerges from the experience that Sampaio’s (2007) proposal for the atenso body for the scene can be a fruitful way to reach the decoloniality of the everyday body.